Women and Political Agency in the Early Modern Low Countries - Nissen, Lidewij; Raeymaekers, Dries (Early Modern Low Countries, 2025)
Politically active women in the early modern period have often been seen as exceptional figures, notable primarily for their ability to influence decision-making despite societal constraints on female authority. Historians have traditionally focused on examples of women from noble, princely, or royal backgrounds, given the prominence and status that enabled their influence. This article argues that expanding the scope of research to include a broader array of social contexts will allow a clearer understanding of early modern women’s roles as legitimate political agents. We propose three approaches to achieve this, highlighting the potential of new digital tools and technologies. By adopting a more systematic analysis that inherently acknowledges women’s political agency, we can gain deeper insights into the dynamics of power in early modern society.